Rural surgery challenges and solutions for the rural surgeon - Wichmann, Matthias W. (Springer, 2011)
Incorporating and balancing advancing subspecialization is a significant challenge of modern surgery. The changes of surgical education and early subspecialization is a smaller spectrum of experience of graduating surgeons joining the rural workforce. Surgeons working in rural and remote hospitals, however, must be proficient in the great breadth of current surgical practice and face a number of challenges and demands that are specific to rural surgery. This textbook provides an update on the evidence and surgical techniques for the experienced rural surgeon and most importantly is a guideline for younger surgeons and surgical trainees joining the general surgical workforce in rural and remote areas around the world.